Learning Video: Efforts to Improve the Quality of Natural Resource Learning for Elementary School Students - Kusumawati, Ni Putu Yogi Sri; Jayanta, I Nyoman Laba; Sukmana, Adrianus I Wayan Ilia Yuda (Universitas Pendidikan Ganesha, 2021)
The low student learning outcomes are caused by the lack of learning media that can motivate students to learn. Therefore, it is necessary to develop learning media that can increase student learning motivation. This study aims to produce products in the form of learning video media on science content, especially natural resource materials. This research is a Research & Development research based on the Borg & Gall model. The subject in this research is learning video media, with the validity of the media as the object of research. This study involved one learning material expert, one instructional media expert, one instructional design expert, and field test preparation (one teacher and six students). The data collection method used questionnaires and questionnaires which were then analyzed using quantitative descriptive analysis. The results of this study indicate that from the aspect of learning materials, aspects of learning media, and aspects of learning design, the qualifications are very good with a percentage of 96.1%. From the aspect of field testing, this media preparation has very good qualifications with a percentage of 97.4%. It was concluded that the learning video media developed was suitable for use in science content, especially natural resource materials in grade IV SD. Therefore, it is recommended to use video media as an alternative in improving the quality of learning natural resource materials in the fourth grade of elementary school.